Determinants of M-Commerce Platform Adoption Among Individuals in South African Township Communities - Mogau Mashishi; Mpho Primus (The Thinker)
Since the COVID-19 pandemic outbreak in 2020, there has been an increase in the adoption of e-commerce (electronic commerce) from which m-commerce (mobile commerce) was born. M-commerce is the use of a mobile phone to purchase goods and services. Most of the South African population resides in townships and rural areas and contributes significantly to the economy. The study researched m-commerce adoption in South African townships by determining the factors that affect m-commerce adoption in South African townships. The study only focused on two townships in Johannesburg: Soweto and Tembisa. A conceptual research model based on the following factors from the UTAUT2 technology model: performance expectancy, hedonic motivation, and facilitating conditions, with social media and trust as two additional constructs. A digital online survey was used to collect respondents’ data, and it was analysed quantitatively using SPSS. The findings of the study are discussed in detail, including testing the hypotheses formulated. Social media and perceived security have a significant, positive effect on the trust of South African township residents to adopt m-commerce platforms. Performance expectancy, hedonic motivation, trust, and facilitating conditions positively affect the intention of South African township residents to adopt m-commerce; however, trust and facilitating conditions were insignificant.